Procriação medicamente assistida com recurso a doação de ovócitos: indicações - Figueira,Rita (2021)
Abstract Introduction: Since the first two successful cases reported in 1984, oocyte donation has become widespread all over the world, currently being an important part of assisted reproductive technologies (ART), with numerous indications that the authors intend to address. Methods: A total of 231 articles were identified through PubMed. A selection was made based on the language, title, abstract and relevance of the articles. 60 articles were included for this review. Discussion: Initially, the main objective of the technique was to treat infertility in women with premature ovarian insufficiency. Over the years, the safety and success of the technique allowed the inclusion of women with advanced reproductive age, after recurrent failure in ART treatments, with recurrent pregnancy loss and with genetic disease not eligible for ART with preimplantation genetic testing, in order to avoid transmission to offspring. In some countries where the law allows it, single men or couples of men can also use this technique. Conclusion: Currently, oocyte donation corresponds to an important and growing percentage of ART cycles worldwide, with a wide range of indications, standing out as an important component of infertility treatment, enabling motherhood and paternity in several cases where it proved impossible.